2013
DOI: 10.1080/14681811.2013.771774
|View full text |Cite
|
Sign up to set email alerts
|

Improving women's sexual health: a quantitative evaluation of an educational intervention for healthcare professionals

Abstract: Forty-three per cent of women in the USA report some type of sexual complaint and these complaints have been shown to negatively impact quality of life and overall wellbeing. With proper training and experience, healthcare professionals are in a unique position to help their patients improve their sexual health. The present study was designed to increase knowledge about female sexual dysfunction by offering a continuing education workshop combining didactic and experiential learning. Healthcare professionals r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 20 publications
2
9
0
Order By: Relevance
“…This is related to the performance accomplishment in Bandura's theory [17]. Previously, it has also been shown that HCPs with experience from patient practice increase their motivation to work on preventive tasks with women [34]. The FGDs revealed that the participants gained confidence in how to detect perinatal depressive symptoms because they had practiced with at least two women.…”
Section: Discussionmentioning
confidence: 89%
“…This is related to the performance accomplishment in Bandura's theory [17]. Previously, it has also been shown that HCPs with experience from patient practice increase their motivation to work on preventive tasks with women [34]. The FGDs revealed that the participants gained confidence in how to detect perinatal depressive symptoms because they had practiced with at least two women.…”
Section: Discussionmentioning
confidence: 89%
“…The findings of this study have highlighted that knowledge regarding VVD among FHCWs has significantly improved by educational intervention. It is evident that training programs are effective in improving knowledge among healthcare workers (Ajuwon, Funmilayo, Oladepo, Osungbade, & Asuzu, 2008; Blair et al, 2013; Goonewardena, Rajapaksha, & Wickremasooriya, 2001). Following an educational intervention on intrapartum and postpartum care, FHCWs have shown a significant improvement of knowledge scores on different stages of labor and care of newborn (Goonewardena et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Bloom's taxonomy provided the conceptual framework for the development of the structure of the educational intervention (objectives, teaching and learning strategies, methods of evaluation) (Williams et al, 2006). A comprehensive review of the literature on STIs, reproductive tract infections and training programs for primary healthcare workers was conducted prior to the development of the content for the educational intervention (Blair et al, 2013; Bradshaw, Lovell, Bee, & Campbell, 2010).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, educational intervention has been shown to significantly increase HCP awareness of the importance of discussing sexual health with patients and may be an appropriate method to increase lubricant-related questioning among HCPs (Blair et al, 2013).…”
Section: Discussionmentioning
confidence: 99%